EDUKASI MENGENAI PENGGUNAAN ANTIBIOTIK YANG RASIONAL DI LINGKUNGAN SMK NEGERI 1 TAMBELANG BEKASI - Shirly Gunawan; Oentarini Tjandra; Susilodinata Halim (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Antibiotics are antimicrobial drugs used to treat bacterial infections. High prevalence of infectious diseases, increasing the use of antibiotics in society. The high rate of antibiotics use without a doctor's prescription makes their use irrational and leads to drug resistance. One of the factors causing drug resistance is the lack of public knowledge about the use of drugs, especially antibiotics. Knowledge plays an important role in shaping certain beliefs, attitudes, and behaviors. The higher the level of education, it is expected that the better the level of knowledge on drug use. Studies to know the level of knowledge of residents using antibiotics, carried out in SMA and SMK Tambelang District Bekasi Regency, show that most respondents have insufficient knowledge (52.4%) of antibiotics. For this reason, PKM activities have been carried out in the form of education on the rational use of antibiotics, which was attended by 53 residents in SMK 1 Tambelang Bekasi, consisting of teachers, students, and educational staff. Before and after education, pretest and post-test were carried out to assess knowledge of antibiotics use. The mean pretest score was 8.08 points, and the post-test mean score was 9.42 points. Statistical analysis showed a mean difference between the pretest and post-test values of 1.34 points with a p-value of 0.008 (p <0.05). With the results obtained, it is expected to increase the knowledge of the residents of SMK 1 Negeri Tambelang Bekasi in the rational use of antibiotics so that it will indirectly reduce the incidence of resistance to antibioticsABSTRAK:Antibiotics are antimicrobial drugs used to treat bacterial infections. High prevalence of infectious diseases, increasing the use of antibiotics in society. The high rate of antibiotics use without a doctor's prescription makes their use irrational and leads to drug resistance. One of the factors causing drug resistance is the lack of public knowledge about the use of drugs, especially antibiotics. Knowledge plays an important role in shaping certain beliefs, attitudes, and behaviors. The higher the level of education, it is expected that the better the level of knowledge on drug use. Studies to know the level of knowledge of residents using antibiotics, carried out in SMA and SMK Tambelang District Bekasi Regency, show that most respondents have insufficient knowledge (52.4%) of antibiotics. For this reason, PKM activities have been carried out in the form of education on the rational use of antibiotics, which was attended by 53 residents in SMK 1 Tambelang Bekasi, consisting of teachers, students, and educational staff. Before and after education, pretest and post-test were carried out to assess knowledge of antibiotics use. The mean pretest score was 8.08 points, and the post-test mean score was 9.42 points. Statistical analysis showed a mean difference between the pretest and post-test values of 1.34 points with a p-value of 0.008 (p <0.05). With the results obtained, it is expected to increase the knowledge of the residents of SMK 1 Negeri Tambelang Bekasi in the rational use of antibiotics so that it will indirectly reduce the incidence of resistance to antibiotics